MicroRNA-loaded biomaterials for osteogenesis - Wang, Jingwei; Cui, Yutao; Liu, He; Li, Shaorong; Sun, Shouye; Xu, Hang; Peng, Chuangang; Wang, Yanbing; Wu, Dankai (Frontiers in Bioengineering and Biotechnology, 2022)
The large incidence of bone defects in clinical practice not only increases the demand for advanced bone transplantation techniques but also the development of bone substitute materials. A variety of emerging bone tissue engineering materials with osteogenic induction ability are promising strategies for the design of bone substitutes. MicroRNAs (miRNAs) are a class of non-coding RNAs that regulate intracellular protein expression by targeting the non-coding region of mRNA3'-UTR to play an important role in osteogenic differentiation. Several miRNA preparations have been used to promote osteogenic differentiation of stem cells. Therefore, multiple functional bone tissue engineering materials using miRNA as an osteogenic factor have been developed and confirmed to have critical efficacy in promoting bone repair. In this review, osteogenic intracellular signaling pathways mediated by miRNA are introduced in detail to provide a clear understanding for future clinical treatment. We summarized the biomaterials loaded with exogenous cells engineered by miRNA and biomaterials directly carrying miRNA acting on endogenous stem cells, and discussed their advantages and disadvantages, providing a feasible method for promoting bone regeneration. Finally, we summarized the current research deficiencies and future research directions of the miRNA functionalized scaffold. This review provides a summary of a variety of advanced miRNA delivery system design strategies that enhance bone regeneration.